Using a daily diary approach to examine the early effects of COVID-19 on daily physical activity bouts and contexts among residents of Colorado and California. Issue 9 (21st June 2021) - Courtney, Jimikaye; Nuss, Kayla; Wang, Shirlene; Do, Bridgette; Dunton, Genevieve
Abstract: COVID-19 restrictions may prevent adults from achieving sufficient physical activity (PA) and may affect PA context. This study examined the early effects of COVID-19 on daily PA bouts and contexts during April–June 2020 using a daily diary approach. Adults ( N = 390) completed daily diary surveys for 28 days assessing number of PA bouts and social (e.g., alone), locational (i.e., home, neighborhood, recreational space), and technology (e.g., using streaming videos) contexts of PA. Mixed-effects models examined the effects of days since the pandemic started (on 3/13/2020), state residence, and demographics on number of daily PA bouts. Models examined demographic and temporal effects on PA context. Participants were 18–77 years, 15% Hispanic/Latino, and 80% female. PA bouts per day decreased significantly over time among Californians versus Coloradans ( b simple = −0.01, p < .001) and Hispanics/Latinos (vs. non-Hispanic Latinos) did fewer PA bouts per day ( b = −0.17, p = .04). Most PA bouts occurred while alone (56.7%), at home (43.4%), or in any neighborhood (40.5%). Older (60+ years) versus younger (<40 years) adults were less likely to do PA with others (odds ratio [OR] = 0.40, 95% confidence interval [CI]: 0.18–0.90). PA bouts in recreational spaces were more common on weekends versus weekdays (OR = 1.59, 95% CI: 1.32–1.92) and were less common among California versus Colorado residents (OR = 0.23, 95% CI: 0.12–0.42). PA bouts decreased from April to June 2020, and these changes disparately affected subgroups. Resources are needed to counteract the negative effects of COVID-19 restrictions intended to slow disease spread on PA. Lay Summary: The COVID-19 pandemic has resulted in closure of spaces for engaging in physical activity, including gyms, parks, and recreation centers. Closure of these spaces likely had a negative impact on activity. We used daily, phone-based surveys to study the effects of COVID-19 on the number of activity bouts individuals did each day, and the context of activity, between April and June 2020. Our study included 390 adults living in California or Colorado who were 18–77 years old, 80% female, and 15% Hispanic/Latino. Californians significantly decreased the number of daily bouts over time, but Coloradans showed no change in daily bouts. Hispanic/Latinos did fewer daily bouts than non-Hispanic/Latinos. Most bouts occurred when people were alone (56.7%), at home (43.4%), or in a neighborhood (40.5%). Adults 60+ years were more likely to do activity alone than with others. Bouts in recreational spaces were more common on weekends versus weekdays, and Californians were less likely to do bouts in recreational spaces than Coloradans. Additional resources are needed to counteract the negative effects of COVID-19 restrictions that intended to slow disease on activity levels, particularly in places with greater restrictions for accessing physical activity spaces.